Eye movements and user emotional experience: a study in interface design - Sun, Ningna; Jiang, Yufei (Frontiers in Psychology, 2025)
The purpose of this study is to explore the correlation between eye movement metrics and user emotional experience metrics during the user’s process of using the interface in a task-oriented manner through an eye-tracking study. Fifty-four participants were recruited, who were divided into two groups and asked to complete the same task using two different sets of interfaces. The two sets of interfaces were proved to have differences in the emotional experience of users before the experiment. The participants’ eye movement data were recorded as they operated, and correlation analyzes were performed using biserial correlation tests. The results show that different interface designs affect the three dimensions of user emotional experience (PAD) and also lead to changes in eye movement patterns as the users complete tasks. Interface designs that elicit higher pleasure will lead to longer duration of fixations. Interface designs that elicit higher arousal will lead to more fixations and higher peak velocity of saccades. Interface designs that elicit higher dominance will lead to longer duration of fixations, fewer fixations and fewer saccades. This study identifies eye movement metrics related to the user emotional experience in interface design that are different from those in other fields, providing a new perspective for the scientific validation of the emotional experience in interface design. The designers can apply the findings to optimize the specific interface design to improve the user’s emotional experience.